Constitucionalismo democrático no Brasil?: a luta de movimentos sociais LGBT pela efetivação de direitos no Poder Judiciário - Nathalia Brito de Carvalho (2017)
The present work has the objective of understanding how the hermeneutical inflows of constitutional interpretation resulting from the observation of the actions of social movements in the Brazilian Judiciary Power are processed. Our object of study is the leading cases of lesbian, gay, bisexual, transvestite, transsexual and transgender movements before the Federal Supreme Court for the recognition of their demands, verifying the plausibility of a reading key in Brazil from the theory of Constitutionalism of Reva Siegel and Robert Post. Part 1 of the research aims to answer how the Supreme Court responds to the demands of LGBT minorities. We have an analysis of the votes of the ministers in different cases, reflecting on their main foundations concomitantly with a brief report about the actions of the LGBT movement around the proposal. Part 2 proposes to theorize the practice of democratic contestation to the constitutional text, presenting the context of disagreement as an essential characteristic of democracy and disappears from the meaning of the Constitution. We work with the hypothesis that the assumptions of the democratic constitutional theory of the authors Reva Siegel and Robert Post are based on theories about the performance of social movements to demonstrate their influence on the change of constitutional meaning. In the end we recognize the need for "judicially enforced rights" and the importance of a commitment to a constitutional reading of the people.